Mapping weaning associated differences in ICU patients needing more than 24 hours of sedation using inhaled/volatile sedation compared to intravenous alternatives - Constantinou, Alexander (My University, 2023)
Patient safety and comfort while ventilated in the intensive care unit (ICU) is a standard objective and often requires the administration of sedation (required by >85% of ICU patients) (Temesgen, 2021). Many aspects of the critical care environment can generate pain and anxiety, including endotracheal intubation, invasive monitoring, frequent care and evaluation by nurses or other practitioners, as well as the administration of treatment (Weinert, 2007). Without sufficient sedation, patients can experience an increased sympathoadrenal discharge with associated hypermetabolism and increased oxygen consumption, agitation and inadvertent removal of the endotracheal tube or lines (Laferriere-Langlois et al., 2017). According to recent guidelines, modern intravenous sedatives include propofol, dexmedetomidine, midazolam, and different combinations of analgesic, hypnotic, and antipsychotic drugs (Barr, 2013). These intravenous sedatives and their active metabolites are organ-dependent for elimination, and this can lead to unpredictable pharmacokinetics and pharmacodynamics, drug accumulation, poor clearance and slow wake-up in critically ill patients. Due to these, patients commonly demonstrating hepatic and renal dysfunction, thus delaying normal systemic clearance of these drugs and possibly leading to oversedation (present in approximately 30% to 60% of ICU patients) (Jackson, 2009). Oversedation is a serious issue that-through clinical research-has been associated with a prolonged mechanical ventilation (MV) time and increased ICU and hospital length of stay (LOS), which further expose patients to an increased risk of infections (Laferriere-Langlois, 2017). On the other hand, the use of volatile agents to anesthetize patients has been used and approved for decades in surgical theatres (Robinson, 2012). Volatile agents such as sevoflurane, isoflurane and desflurane have well-known useful pharmacological properties but are actually underused in the ICU, mainly due to technical issues with administering them accurately ( Laferriere-Langlois, 2017). Recently, there is growing interest in volatile anesthetics in the ICU as they offer potential advantages over the previously mentioned intravenous sedation (Meiser et al., 2010). The most recently developed halogenated agents, including isoflurane, sevoflurane and desflurane, have potential pharmacokinetic and pharmacodynamic advantages for critically ill patients. Firstly, they have a rapid onset of action and do not have time to accumulate much in tissues, allowing a fast offset, therefore possibly having a role in reducing awakening time and allowing earlier extubation. Secondly, their sedation effect is independent of the state of the kidneys and liver, which often, as mentioned before, are usually found to be impaired in ICU patients (Jerath et al., 2015). Since it has shown some promise, this previously off-label therapy has now been actually endorsed in national and international guidelines (eg, German guidelines, and guidelines from the PanAmerican and Iberian Federation of Societies of Critical Medicine and Intensive Therapy), while in parallel, the Sedaconda anaesthetic conserving device, formerly known as AnaConDa, has been developed for the accurate delivery of inhaled anaesthetics (Celis-Rodríguez E, 2020).This takes cares of the previous technical issue that was mentioned (administering said inhaled agents accurately in the ICU environment) at least in those countries(Mainly: Belgium, Norway, Denmark, Spain, Finland, United Kingdom, France, Sweden, The Netherlands, Germany) where the aforementioned specific devices have been developed and approved for use with modern halogenated/inhaled agents. Traditionally, sedation is managed by physicians whom give an order regarding the scheme of sedation that will be used, which is then followed by nurses who document and communicate the different sedation scores to the physician and then receive an appropriate dose-adjusted plan according to the patient's condition from the doctor. Passively executing orders from the physician without being informed is not ideal for continuously evaluating and observing sedation, so an alternative could be the adoption of a nurse led programmed sedation management since it has also been found in a study by Lu et al., 2022 to reduce excessive or insufficient sedation and improve sedative effects.
Keywords: Patient safety; intensive care unit (ICU)